RWL Water awarded Mexican BOT desalination project. Issue 10 (October 2015) - Unknown
Abstract : RWL Water and its Mexican partners Libra Ingenieros and RJ Ingenieria are to build, finance, operate and transfer (BOT) a seawater desalination plant for the State Water Commission of Baja California in Mexico.